3065 A1BG and ITIH4 proteins are upregulated on HDL of youth with type 1 diabetes and correlate with glycemic control. (27th March 2019) - Gourgari, Evgenia; Gordon, Scott; Ma, Junfeng; Playford, Martin; Mehta, Nehal; Goldman, Radoslav; Remaley, Alan
Abstract : OBJECTIVES/SPECIFIC AIMS: Our objective was to compare the proteomics of HDL between youth with T1DM and healthy controls (HC). METHODS/STUDY POPULATION: We did chromatography-based HDL purification and SWATH-MS-based proteomic quantitation. Proteomic alterations of HDL fractions and their association with glycemic control was examined. Study population: 26 patients with T1DM and 13 HC. RESULTS/ANTICIPATED RESULTS: We quantified 78 proteins in isolated HDL, using mass spectrometry and label-free SWATH quantification. Youth with T1DM had significantly higher protein levels of A1BG (P = 0.008), A2AP (P = 0.0448), APOA4 (P = 0.0366), CFAH (P = 0.0476), FHR2 (P = 0.0005), ITIH4(P = 0.01), PGRP2 (P = 0.0167) and lower levels of ALBU (P = 0.0164) and CO3 (P = 0.019) compared to HC. A1BG (r=0.541, P<0.001) and ITIH4 (r=0.357, P = 0.026) were significantly positively correlated with HbA1c. DISCUSSION/SIGNIFICANCE OF IMPACT: Youth with T1DM have proteomic alterations of their HDL compared to HC, despite similar concentration of HDL cholesterol, that might affect the cardioprotective mechanisms of HDL. Future efforts should focus on investigating the role of these HDL associated proteins in regard to HDL function and their role in CVD risk in patients with T1DM.